Risk score predicts high‐grade prostate cancer in DNA‐methylation positive, histopathologically negative biopsies. Issue 12 (28th April 2016) - Van Neste, Leander; Partin, Alan W.; Stewart, Grant D.; Epstein, Jonathan I.; Harrison, David J.; Van Criekinge, Wim
Abstract : BACKGROUND: Prostate cancer (PCa) diagnosis is challenging because efforts for effective, timely treatment of men with significant cancer typically result in over‐diagnosis and repeat biopsies. The presence or absence of epigenetic aberrations, more specifically DNA‐methylation of GSTP1, RASSF1, and APC in histopathologically negative prostate core biopsies has resulted in an increased negative predictive value (NPV) of ∼90% and thus could lead to a reduction of unnecessary repeat biopsies. Here, it is investigated whether, in methylation‐positive men, DNA‐methylation intensities could help to identify those men harboring high‐grade (Gleason score ≥7) PCa, resulting in an improved positive predictive value. METHODS: Two cohorts, consisting of men with histopathologically negative index biopsies, followed by a positive or negative repeat biopsy, were combined. EpiScore, a methylation intensity algorithm was developed in methylation‐positive men, using area under the curve of the receiver operating characteristic as metric for performance. Next, a risk score was developed combining EpiScore with traditional clinical risk factors to further improve the identification of high‐grade (Gleason Score ≥7) cancer. RESULTS: Compared to other risk factors, detection of DNA‐methylation in histopathologically negative biopsies was the most significant and important predictor of high‐grade cancer, resulting in a NPV of 96%. In methylation‐positive men, EpiScore was significantly higher for those with high‐grade cancer detected upon repeat biopsy, compared to those with either no or low‐grade cancer. The risk score resulted in further improvement of patient risk stratification and was a significantly better predictor compared to currently used metrics as PSA and the prostate cancer prevention trial (PCPT) risk calculator (RC). A decision curve analysis indicated strong clinical utility for the risk score as decision‐making tool for repeat biopsy. CONCLUSIONS: Low DNA‐methylation levels in PCa‐negative biopsies led to a NPV of 96% for high‐grade cancer. The risk score, comprising DNA‐methylation intensity and traditional clinical risk factors, improved the identification of men with high‐grade cancer, with a maximum avoidance of unnecessary repeat biopsies. This risk score resulted in better patient risk stratification and significantly outperformed current risk prediction models such as PCPTRC and PSA. The risk score could help to identify patients with histopathologically negative biopsies harboring high‐grade PCa. Prostate 76:1078–1087, 2016 . © 2016 The Authors. The Prostate Published by Wiley Periodicals, Inc.